Mathematics Education in India through Policy Documents - B, Madhu; K, Biju (JOURNAL OF INDIAN EDUCATION, 2023)
he Government of India approved the National Education Policy 2020 in July 2020, which envisions many systemic changes in school and higher level education. Mathematics education is considered one of the significant components of school education as a compulsory subject up to Class X after the Kothari Commission, which continued to be the most difficult one. In this paper, we observed developments in mathematics education in India in accordance with the policy documents from the Kothari commission up to the NEP 2020. A critical analysis of the policy documents was done to portray the significant challenges of Mathematics education in Indian schools, which still prevail. We expect that this paper will contribute to the on-going discussions about the National Curriculum Framework while offering valuable inputs for the development of mathematics textbooks.